PERLINDUNGAN HUKUM PEKERJA TERKAIT KOMPENSASI BERAKHIRNYA MASA PKWT BERDASARKAN PP NO 35 TAHUN 2021 - Riyadi, Sugeng; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
Abstract: This research was conducted with the aim of finding out and understanding how legal protection is for workers who are not given compensation money at the end of a certain time work agreement (PKWT). Based on the research results obtained, it shows that compensation money at the end of the certain time work agreement (PKWT) must be given by employers as a form of respect for employees' rights after the contract ends at the company where they work. If the company does not provide compensation to employees who work based on a Specific Time Work Agreement, the company may be subject to sanctions in the form of fines, payment of outstanding compensation obligations, or demands for compensation. for losses suffered by employees.Keywords: PP No.35 of 2021,PKWT compensation,PKWT Protection